Figures of Democratic Socialism in the First Quarter of the 20th Century: Socio-demographic Characteristics - L. Protasova, Olga; G. Pirozhkova, Irina (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study is a comprehensive research of the Russian socialist parties at the beginning of the 20th century, both in terms of formal statistical indicators and in addressing the fates of their activists. The employed unique biographical material contributes to the popularization of the case history described and arouses interest in people who have made a significant contribution to the formation of civic culture and democracy in Russia. The problem statement of the research is due to the demand for a synergistic approach in modern historical science, which allows synthesizing the methods of political science, sociology, and psychology, as well as using mathematical methods in processing the results. Through the above methods, as well as comparison and grouping, a cohort analysis (a sample of about 3 thousand people) on the main socio-demographic characteristics of both well-recognized and ordinary members of the leading political parties of Russia was carried out. The presented article reviews how the choice of political orientation was influenced by the age of the activist, the social stratum, ethnical and partly confessional affiliation, level of education, occupation, and other socio-demographic factors. The conducted study resulted in the following conclusion: the general conditional ‘portrait’ of a socialist at the beginning of the 20th century is quite amorphous, which is largely due to the incompleteness at the time of the formation of the entire political elite and of embedding it in the political culture of the country. Socialism in terms of the number of supporters prevailed over other ideologies in Russia at the beginning of the 20th century, but its democratic segment in the political struggle lost to the anti-democratic, totalitarian direction represented by the Bolsheviks.